FERROCARRILES EN LA ZONA AUSTRAL DE CHILE, 1869-1973 - Mateo Martinic B. (Historia (Santiago), 2005)
En este artículo se entrega una visión completa acerca de los ferrocarriles construidos y explotados en la región austral de Chile y se ofrece asimismo una explicación sobre su modesta expresión histrica, cosa notable en un territorio como la Patagonia chilena en cuya colonización y desarrollo ulterior fue importante la utilización de la tecnología industrial moderna. Se dan a conocer también algunas interesantes iniciativas ferrocarrileras que no llegaron a materializarse In spite of the important development in Chilean Patagonia between circa 1870 an 1973, particulary in the old Magellan Territory, an almost surprising fact was that in between many incorporated industrial technology the railroad, a paradigm of modernity, had a scarce representation. In this paper, a complete review about railroads settled and exploted in southernmost Chile is done and a explanation of its modest expression and some interesting projects that necer became materialized which explains the emptiness in the historical information on the subject